1979
DOI: 10.1073/pnas.76.5.2460
|View full text |Cite
|
Sign up to set email alerts
|

Human breast carcinoma antigen is immunologically related to the polypeptide of the group-specific glycoprotein of mouse mammary tumor virus.

Abstract: We have shown [Mesa-Tejada, R., Keydar, I., Ramanarayanan, M., Ohno, T., Fenoglio (14). Because at most five sections are stained from each breast tumor, the percentage of positives detected must be an underestimate.It was of course gratifying to have extended to the protein level the relationship between human breast cancer and MMTV that was initially discovered in terms of nucleic acid sequence homology. The etiologic implications of these findings are of obvious interest but our immediate concern is the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…It already has been shown that antigen from human breast carcinomas immunologically crossreacts with the protein moiety of gp52 and not with the carbohydrate portion of this MMTV glycoprotein (3). Perhaps a similar situation holds in the present case.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…It already has been shown that antigen from human breast carcinomas immunologically crossreacts with the protein moiety of gp52 and not with the carbohydrate portion of this MMTV glycoprotein (3). Perhaps a similar situation holds in the present case.…”
Section: Resultssupporting
confidence: 67%
“…Substantial evidence has accumulated in the past few years for the presence of MMTV gp52-related proteins in human mammary carcinomas (3,4) and in human mammary carcinoma cell lines such as T47D or MCF-7 (6, 7). We have shown that such antigens also are present both in the viral particles released by the T47D cell line and among the soluble proteins that are shed by these cells (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, using immunoperoxidase staining, Mesa-Tejada et al (5) found that antigen reacting with antibody to the envelope glycoprotein of MuMTV (gp52) could be detected in breast cancer tissue. Ohno et al (6) have now demonstrated that this crossreactivity is directed to the protein moiety ofgp52 and not the carbohydrate.…”
mentioning
confidence: 99%
“…Furthermore, an antigen immunologically related to the group-specific antigen gp52 (a 52,000-dalton envelope glycoprotein) of MMTV has been detected (8,9) in paraffin sections of human breast cancer by peroxidase immunocytochemistry. The fact that it is the polypeptide, rather than the polysaccharide, portion of gp52 that is responsible for the immunological reactivity with the human breast cancer antigen (10) adds additional significance to the biological similarities between the human and the murine mammary neoplasias.…”
mentioning
confidence: 99%